In-Silico Studies Of Microrna In Glycine Max And Brassica Napus - S.DUBEY (International Journal of Pharma and Bio Sciences, 2011)
MicroRNAs (miRNAs) are very small non-coding molecules of RNA. These are gene products of about 19-25 nucleotides in length which are evolutionarily conserved molecules and expressed in a wide variety of organisms from plants, viruses and animals. MicroRNAs play an important regulatory role in post-transcriptional gene modification. These are derived from larger hairpin RNA precursor molecules and are more conserved in the secondary structure rather than the primary structure.